2003
DOI: 10.1086/378038
|View full text |Cite
|
Sign up to set email alerts
|

The Hot Core around the Low-Mass Protostar IRAS 16293-2422: Scoundrels Rule!

Abstract: While warm dense gas is prevalent around low-mass protostars, the presence of complex saturated molecules-the chemical inventory characteristic of hot cores-has remained elusive in such environments. Here we report the results of an IRAM 30 m study of the molecular composition associated with the low-mass protostar IRAS 16293Ϫ2422. Our observations highlight an extremely rich organic inventory in this source with abundant amounts of complex O-and N-bearing molecules such as formic acid, HCOOH, acetaldehyde, CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
542
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 503 publications
(569 citation statements)
references
References 28 publications
24
542
1
2
Order By: Relevance
“…van Dishoeck et al (1995) and Cazaux et al (2003) is a low-mass equivalent to the high-mass hot cores, and there are at least five other low-mass protostars where complex molecules such as HCOOCH 3 and CH 3 OCH 3 are detected by Bottinelli et al (2004), Jørgensen et al (2005) and van der Marel et al (2011). Arce et al (2008) also detected complex molecules in a low-mass outflow andÖberg et al (2010) recently detected HCOOCH 3 in a cold and quiescent part of a low-mass star forming region that probably has been illuminated by UV through a protostellar outflow cavity.…”
Section: Ice Formation In Clouds and Cloud Coresmentioning
confidence: 99%
“…van Dishoeck et al (1995) and Cazaux et al (2003) is a low-mass equivalent to the high-mass hot cores, and there are at least five other low-mass protostars where complex molecules such as HCOOCH 3 and CH 3 OCH 3 are detected by Bottinelli et al (2004), Jørgensen et al (2005) and van der Marel et al (2011). Arce et al (2008) also detected complex molecules in a low-mass outflow andÖberg et al (2010) recently detected HCOOCH 3 in a cold and quiescent part of a low-mass star forming region that probably has been illuminated by UV through a protostellar outflow cavity.…”
Section: Ice Formation In Clouds and Cloud Coresmentioning
confidence: 99%
“…First discovery was the detection of large saturated COMs such as HCOOCH 3 , (CH 3 ) 2 O, and C 2 H 5 CN in the low-mass star-forming region, IRAS16293-2422 (Cazaux et al 2003), revealing that the hot-core like chemistry is also occurring even in a low-mass source. Furthermore, the interferometric observations showed that these molecules are distributed within a few 100 AU region (at temperature of ∼ 100 K) around the protostar (Bottinelli et al 2004b;Kuan et al 2004).…”
Section: Hot Corino Chemistry and Warm Carbon-chain Chemistrymentioning
confidence: 99%
“…Just as in the case of the hot core chemistry in high-mass star forming regions, saturated COMs are formed on dust grains during cold and warm-up phases (Garrod & Herbst 2006), and are liberated into the gas phase in a small hot region (a few 100 AU) around the protostar, called hot corino. Now four Class 0 protostars (IRAS 16293-2422, NGC1333 IRAS4A, IRAS4B, and IRAS2A) are known to harbor hot corinos (Cazaux et al 2003;Bottinelli et al 2004a;Jørgensen et al 2005;Sakai et al 2006;Bottinelli et al 2007). …”
Section: Hot Corino Chemistry and Warm Carbon-chain Chemistrymentioning
confidence: 99%
“…One of the most interesting recent developments in the astrochemistry of low-mass protostars has undoubtedly been the detections on complex organics in low-mass protostars (Cazaux et al 2003;Bottinelli et al 2004;Sakai et al 2006). A parallel has been proposed between these "hot corinos" and the high-mass protostellar "hot cores" related to the evaporation of icy-mantles on scales where the dust and gas is heated to (Jørgensen et al 2005a).…”
Section: The Innermost Regions: Hot Corinos and Disksmentioning
confidence: 99%